Fuzzy Maximal and Minimal Α-Clopen Sets - Sankari, M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The aim of the paper is to introduce the notions of fuzzy maximal and fuzzy minimal α -clopen sets in fuzzy topological spaces. The notions of fuzzy maximal and minimal α -clopen sets are respectively independent to the notions of fuzzy maximal and fuzzy minimal α -open (resp.closed) sets. Further, fuzzy maximal α -clopen and fuzzy minimal α -clopen sets are discussed using fuzzy α -disconnectedness.